Detection of Electronic Devices Using FMCW Nonlinear Radar - Kyuho Cha; Sooyoung Oh; Hayoung Hong; Hongsoo Park; Sun K. Hong (Sensors, 2022)
Nonlinear radars can be utilized to detect electronic devices, which are difficult to detect with conventional radars due to their small radar cross sections (RCS). Since the receiver in a nonlinear radar is designed to only receive harmonic or intermodulated echoes from electronic devices, it is able to separate electronic devices from non-electronic scatters (clutter) by rejecting their echoes at fundamental frequencies. This paper presents a harmonic-based nonlinear radar scheme utilizing frequency-modulated continuous-wave (FMCW) signals for the detection of various electronic devices at short range. Using a laboratory experiment setup for FMCW radar at S-band for Tx (C-band for Rx), measurements are carried out to detect electronic devices of various sizes. The results show that the detection of small electronic devices is possible with nonlinear FMCW radar when appropriate system parameters are selected. Furthermore, we also discuss the maximum detectable range estimation for electronic targets using the radar range equation for FMCW nonlinear radar.